Análisis de la cartera vencida del servicio de agua potable del Municipio de Chillanes año 2018 -2019 - Monar Camacho, Jennifer Andreina (2020)
The present case study focusing on the Subline of investigation of Tax Financial Management and Social Commitment, and using the descriptive research method which, allowed to evaluate the problems that the Autonomous Decentralized Municipal Government of the Canton Chillanes is going through with respect to the overdue water portfolio drinking during the years 2018 - 2019. The objective of this study is to analyze said overdue portfolio, which has suffered variations from one year to another causing it to increase, this situation evidenced a lack of control over the collection processes, and the lack of of drinking water meters or the maintenance or replacement of the same that are found to be damaged in various sectors of rural and urban areas which leads to the lack of control of drinking water consumption, another variant is the lack of a Municipal ordinance that promotes the culture of payment compliance of the inhabitants, since having a low interest rate for default, It affects that the taxpayer does not have this obligation to comply with punctual payment, and therefore they only cancel this debt when they have to update the operating permits of the commercial premises, or when they need to carry out the sale of some real estate, all These collection factors influence the institutional economy since these values are not received by the drinking water rate, causing a lack of works to improve the service provided to the community. This is why the Municipal GAD requires the implementation of collection strategies by offering users payment facilities.